Ganoderma lucidum Polysaccharide (GLP) Inhibited the Progression of Oral Squamous Cell Carcinoma via the miR-188/BCL9/β-Catenin Pathway - Zhigang Zeng; Kaiyan Xiao (Advances in Polymer Technology)
Objective. The effects of Ganoderma lucidum polysaccharide (GLP) on the proliferation and migration of oral squamous cell carcinoma (OSCC) cells (HSC-3) were investigated in this study. Methods. Oral squamous cell carcinoma (OSCC) cells (HSC-3) were cultured in vitro and were treated with different concentrations of GLP. CCK-8 assay and scratch assay were then used to detect the inhibitory effect of GLP on these cells. qRT-PCR and western blot were used to measure the expression changes of the genes involved in the miR-188 and β-catenin signaling pathways. Results. GLP had significant cytotoxicity to HSC-3 cells and was capable of inhibiting the proliferation and migration of HSC-3 cells. GLP upregulated the expression of miR-188 in HSC-3 cells and via which inhibited the proliferation and migration of HSC-3 cells. In addition, miR-188 inhibited the activation of the β-catenin signaling pathway through its target BCL9. Conclusions. GLP inhibited the proliferation and migration of OSCC cells (HSC-3) by regulating the miR-188/BCL9/β-catenin signaling pathway. The results in this study provided a theoretical basis for the treatment of OSCC with GLP.